(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article analyzes the socio-psychological impact of artificial intelligence (AI) technologies on personal value systems. Based on international and local experience, the study examines both the positive and negative consequences of AI implementation in education, culture, and social relations. In addition, issues related to AI ethics, algorithmic fairness, privacy protection, and technological dependence are evaluated using scientific sources, and practical recommendations are proposed.